Airports, Cities, and the Jet Age US Airports Since 1945 - Bednarek, Janet R.; SpringerLink (Online service) (Cham : Springer International Publishing (Imprint), 2016)
This book explores the relationship between cities and their commercial airports. These vital transportation facilities are locally owned and managed and civic leaders and boosters have made them central to often expansive economic development dreams, including the construction of architecturally significant buildings. However, other metropolitan residents have paid a high price for the expansion of air transportation, as battles over jet aircraft noise resulted not only in quieter jet engine technologies, but profound changes in the metropolitan landscape with the clearance of both urban and suburban neighborhoods. And in the wake of 9/11, the US commercial airport has emerged as the place where Americans most fully experience the security regime introduced after those terrorist attacks. .
Introduction: Cities, Airports and the Jet Age -- Part One -- Chapter One From 30,000 Feet: Airports and Aviation History Since 1945 -- Chapter Two Closer to the Ground: Airport Ownership and Finance -- Part Two -- Chapter Three Response to the Jet Age: Federal-Local Interaction and the Shaping of the Aviation Landscape -- Chapter Four Airports for the "Jet Age": Expansion, Iconic Architecture and Airport Malls -- Part Three -- Chapter Five The Broad Problem of Airport Noise: Airports, the Courts, the Federal Government, and the Environment -- Chapter Six Cities and Jet Noise: On the Ground and in the Air, How to Tame the Planes that Roared -- Part Four -- Chapter Seven Airport Security: Hijackers, Terrorists, Religious Groups and the Constitution -- Conclusion.
Keywords: United States-History.; History; Cities and towns-History.; Sociology, Urban; History of Science; Urban Studies/Sociology.